Pembangunan Ekonomi Pedesaan (Studi pada Sebuah Inovasi dan Realisasi Ekonomi Desa Banmaleng Gili Raja Sumenep Madura) - Misbahul Munir; Ach Faqih Supandi (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2021)
This research method used descriptive qualitative methods (Qualitative Research).The results of this study were in the application of the village economy, the family values that were still thick in the villages must be further enhanced and adhered to as a guide and boundaries so there was no friction between village members (village officials) and the village community itself. With existing institutions or habits, rural communities were usually able to cooperate without significant friction which results in unfair competition in the economic improvement of the village community.